2020
DOI: 10.3389/fncel.2020.563428
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin-Releasing Factor Modulates the Facial Stimulation-Evoked Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission in vivo in Mice

Abstract: Corticotropin-releasing factor (CRF) is an important neuromodulator in central nervous system that modulates neuronal activity via its receptors during stress responses. In cerebellar cortex, CRF modulates the simple spike (SS) firing activity of Purkinje cells (PCs) has been previously demonstrated, whereas the effect of CRF on the molecular layer interneuron (MLI)–PC synaptic transmission is still unknown. In this study, we examined the effect of CRF on the facial stimulation–evoked cerebellar cortical MLI-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Microscope slides with slices were then washed 3 times in PBS covered with a coverslip and sealed with nail polish. Fluorescence images were acquired by confocal laser scanning microscope (Nikon C2, Tokyo, Japan) ( Mi et al, 2018 ; Wu et al, 2020 ). A large region image including Crus II was obtained on Nikon C2 laser confocal system with 10 × objective.…”
Section: Methodsmentioning
confidence: 99%
“…Microscope slides with slices were then washed 3 times in PBS covered with a coverslip and sealed with nail polish. Fluorescence images were acquired by confocal laser scanning microscope (Nikon C2, Tokyo, Japan) ( Mi et al, 2018 ; Wu et al, 2020 ). A large region image including Crus II was obtained on Nikon C2 laser confocal system with 10 × objective.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical study has revealed that both CRF-R1 and CRF-R2 were expressed in adult rat cerebellum (Swinny et al, 2003). CRF release from CRFergic mossy ber terminals in granular layer and molecular layer could regulate mossy ber-granule cell, parallel ber-PC and parallel ber-MLIs synaptic transmission and long-term plasticity Wang et al, 2018;Wu et al, 2020). We recently found that CRF increases excitability of MLIs, resulting in a signi cant enhancement of the facial stimulation-evoked MLI-PC synaptic transmission via activation of CRF-R1 in vivo in mice, suggesting that CRF modulates MLI-PC synaptic transmission and long-term plasticity and play a critical role in motor learning in living animals (Wu et al, 2020).…”
Section: Activation Of Crf-r1 Modulates Cerebellar Mli-pc Synaptic Tr...mentioning
confidence: 99%
“…CRF release from CRFergic mossy ber terminals in granular layer and molecular layer could regulate mossy ber-granule cell, parallel ber-PC and parallel ber-MLIs synaptic transmission and long-term plasticity Wang et al, 2018;Wu et al, 2020). We recently found that CRF increases excitability of MLIs, resulting in a signi cant enhancement of the facial stimulation-evoked MLI-PC synaptic transmission via activation of CRF-R1 in vivo in mice, suggesting that CRF modulates MLI-PC synaptic transmission and long-term plasticity and play a critical role in motor learning in living animals (Wu et al, 2020). Interestingly, our present results showed that CRF failed to prevent the facial stimulation-induced MLI-PC LTD in mouse cerebellar cortex in the absence of CRF-R1 activity, suggesting that activation of CRF-R1 impaired the expression of MLI-PC LTD.…”
Section: Activation Of Crf-r1 Modulates Cerebellar Mli-pc Synaptic Tr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both CRF-R1 and CRF-R2 are expressed in the cerebellum of adult rodents [ 7 9 ]. CRF-R1 is found in all lobules of the cerebellar cortex, including Purkinje cells (PCs), molecular layer interneurons (MLIs), Golgi cells and granule cells [ 10 12 ]. In contrast, CRF-R2 has been found in the cerebellar cortical molecular layer, such as in parallel fibers and their terminals [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%